Optimization of Consensus Deliberation in the Settlement of Village Assets in the Form of Land Disputes Based on Justice - Fadhalia, Nyata Nabela; Jamin, Mohammad; Jaelani, Abdul Kadir (Green Publisher Indonesia, 2025)
Critical for rural development, village land assets often trigger disputes due to ambiguous boundaries and competing claims. Despite legal frameworks like Permendagri No. 1/2016 and Book C of the Village, consensus-based deliberation (musyawarah) frequently fails, necessitating court intervention. This study investigates the causes of unsuccessful non-litigation resolutions and formulates justice-based optimization strategies for deliberation in Larikrejo Village, Central Java. Using interviews and observations, empirical legal research with qualitative analysis was conducted to examine socio-legal dynamics between the Village Government and communities. Disputes stem from historical boundary ambiguities and power asymmetries, with mediation failing due to entrenched distrust. Courts provided binding solutions, but hybrid models (deliberation + litigation) are proposed to enhance fairness and efficiency. The study advocates for institutional training in mediation (BPD), legal empowerment for villagers, and cross-regional comparisons to refine hybrid dispute resolution, balancing local traditions with legal enforcement.